Juegos tradicionales y su influencia en el desarrollo de habilidades socioafectivas en educación inicial II - Espinoza Herrera, Karelis Nicole (2024)
Traditional games throughout history have been used by generations to promote social relationships, however, these games can be applied in education for learning purposes among which socio-affective skills can be adequately developed, therefore This research aims to analyze traditional games as didactic resources for the development of socio-affective skills of children in early education II. In the “Emigdio Esparza Moreno” Educational Unit, this problem could be observed, for which a documentary and descriptive investigation was used, a synthetic analytical method was applied together with a non-experimental design with a mixed approach for the adequate preparation of this project. Traditional games in the educational field had a favorable result in the development of socio-affective skills since they allow children to interact with each other, helping them relate to others in an effective way. With the information analyzed, the conclusion is reached that it is important to use traditional games in favor of education since, as analyzed, it favors and promotes the development of the socio-affective ability of children, thus ensuring that their school performance does not decrease.